A cytogenetic and molecular study of a series of 45, X fetuses and their parents. Issue 3 (March 1991) - Cockwell, A; MacKenzie, M; Youings, S; Jacobs, P
Abstract : The parental origin of the single X chromosome in 10 45, X fetuses was studied using DNA restriction fragment length polymorphisms. In six the single X was maternal in origin, in one it was paternal, and in one the results were consistent with a paternal origin. Therefore the parental origin of the X in 45, X fetuses that survive to the second or third trimester of pregnancy is similar to that of spontaneous abortions and live births with a 45, X constitution. The mothers of two of the fetuses were themselves found to have an abnormal sex chromosome complement, but in neither case did it appear to be related to the chromosome abnormality in the fetus.